2013
DOI: 10.1039/c3tb20679c
|View full text |Cite
|
Sign up to set email alerts
|

Polythiophene-g-poly(ethylene glycol) graft copolymers for electroactive scaffolds

Abstract: The properties, microscopic organization and behavior as the cellular matrix of an all-conjugated polythiophene backbone (PTh) and well-defined poly(ethylene glycol) (PEG) grafted chains have been investigated using different experimental techniques and molecular dynamic simulations. UV-vis spectroscopy has been used to determine the optical band gap, which has been found to vary between 2.25 and 2.9 eV depending on the length of the PEG chains and the chemical nature of the dopant anion, and to detect polaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 59 publications
2
29
1
1
Order By: Relevance
“…In contrast, the contact angle obtained for 75:25 PTh 3 * ‐ g ‐PEG 2000 , 67 ± 5°, indicates an enhancement of the surface hydrophilicity due the PEG chains. The contact angle reported for PTh 5 ‐ g ‐PEG 2000 , 76 ± 5°, is intermediate between those measured for 75:25 and 50:50 PTh 3 * ‐ g ‐PEG 2000 films.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…In contrast, the contact angle obtained for 75:25 PTh 3 * ‐ g ‐PEG 2000 , 67 ± 5°, indicates an enhancement of the surface hydrophilicity due the PEG chains. The contact angle reported for PTh 5 ‐ g ‐PEG 2000 , 76 ± 5°, is intermediate between those measured for 75:25 and 50:50 PTh 3 * ‐ g ‐PEG 2000 films.…”
Section: Resultscontrasting
confidence: 55%
“…This band, which corresponds to the π‐π * transition, have been used to approximate the optical π‐π * lowest transition energy ( E g ) by estimating the onset wavelength ( λ onset = 573 and 566 nm for the 75:25 and 50:50 copolymer, respectively), the resulting values being 2.16 (75:25) and 2.19 eV (50:50). These E g gaps are slightly lower than those reported for PTh 5 ‐ g ‐PEG 1000 and PTh 5 ‐ g ‐PEG 2000 doped with ClO 4 − (2.25 and 2.29 eV, respectively), which were estimated using the same methodology . Accordingly, the π‐electron delocalization in graft copolymers made of PTh and PEG increases with decreasing PEG/Th ratio.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Grande et al reported the first study on grafting of polymethylmethacrylate and polystyrene brushes from an electrochemically produced polyterthiophene backbone. 17 Since then, grafted brushes have been used to improve CP hydrophilicity, 18 modulate electrochemical behavior of CP-based biosensors towards analytes of interest, 19 and recently to introduce antifouling behavior. 20 An additional layer of control over the surface properties can be added through the use of stimuli-responsive polymer brushes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, soluble PTh derivatives have been combined with biodegradable and biocompatible insulating polymers to fabricate 2D [37][38][39][40][41] and 3D [42][43][44] scaffolds; hydrophilic and biocompatible poly(ethylene glycol) (PEG) chains have been grafted to PTh chains to fabricate amphiphilic PTh bottle-brush copolymers; [45][46][47] and biomolecules, such as small peptides 48 or proteins, [49][50][51] have been immobilized into PTh matrices using in situ polymerization approaches. In this work, we combine our interest in Schiff bases with our expertise on bioactive PThs to investigate a new approach oriented towards the development of new platforms for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%